Pengaruh Media Pembelajaran Interaktif Mentimeter Terhadap Keaktifan, Motivasi, dan Hasil Belajar Siswa Dalam Pembelajaran Daring Di Kelas X Program Keahlian Multimedia Mata Pelajaran Teknik Pengolahan Audio Dan Video SMK Negeri 7 Malang - Nia Amanda Putri; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The research was motivated by a pandemic situation which result in the limitations of teachers and students in carrying out learning and decreased learning motivation so that they were less active in the online teaching and learning process because the media used in learning was less interactive. Research was conducted at SMK Negeri 7 Malang Multimedia expertise program using website-based Mentimeter Learning Media to support online learning. The aim of this research is to increase student activeness and motivation by using Mentimeter interactive learning media as an alternative media in online learning. The research used True Experiment Design by using two classes as the experimental class and the control class. Data collection techniques by observation, interviews, questionariess, and pretest and posttest. The majors used for research are class X Multimedia 1 and X Multimedia 2. Data processing using Excel and SPSS version 26 getting the results of the Independent Sample T-Test motivation of 0,180 > 0,05 proves that there is no difference between the experimental class and the control class. For activeness with a value of 0,493>0,05, it proves that there is no difference between the experimental class and the control class results that a simple linier regression test with a significance value of 0,292>0,05 proves that Mentimeter media has no effect on student motivation, value significance 0,221>0,05 proves that Mentimeter media has no effect on student activity. The significance value of 0,03, the Mann Whitney test proves that posttest scores of the experimental and control class 77.3 and the control class 65,5.